Simplifying Complexity. Rhetoric and the Social Politics of Dealing with Ignorance - Yoos, George E. (De Gruyter, 2015)
Simplifying complexity explores how to eliminate ignorance, which in the view of the author, is the purpose of the sciences and technologies and their consequent developments. More specifically, the book deals with the plurality of the sciences and technologies. It is about the way in which each of them develops around the prosthetics of printed languages and the models used as visual aids to help us create new modes of communication to understand and solve human problems. Consequently, the task is to simplify the complexity that we find in different sciences, both social and physical. In his collection of essays, George E. Yoos surveys a number of different models that have evolved from the innate, biological forms of grammar, logic, and modes of orientation. He investigates the evolution of socially constructed systems of numeracy and measurement that have evolved and developed in different languages for the use in scientific and technological communication. He identifies methods derived from three distinct personal experiences: the use of types of prosthetic, mnemonic, and attention controlling devices, in order to yield simpler perspectives of complex states of affairs. George E. Yoos, emeritus professor, is a legend in the field of rhetoric. Founder and editor of the Rhetoric Society Quarterly [1972-1985], author of Reframing Rhetoric [2007], Politics and Rhetoric [2009], and fellow of the Rhetoric Society of America.